Building the Positive Emotion-Resilience-Coping Efficacy Model for COVID-19 Pandemic - Ke, Guek Nee; Grajfoner, Dasha; Wong, Rachel Mei Ming; Carter, Stephen; Khairudin, Rozainee; Lau, Wee Yeap; Kamal, Khalil Anwar; Lee, Shen Chieng (Frontiers in Psychology, 2022)
The world faces unprecedented challenges because of the Coronavirus Disease 2019 (COVID-19). Existing theories of human flourishing and coping efficacy are too broad and general to address COVID-19 unprecedented mental health challenges. This study examined two main objectives, first the associations between psychological outcomes (i.e. depression, anxiety, and stress) and psychological well-being of this phenomenon, and second, moderating and mediating factors emotions, resilience and coping self-efficacy. A nationwide survey was carried out with a Malaysian sample (n = 920). Participants completed an on-line survey that assessed psychological outcomes, psychological well-being, positive-negative emotions, resilience, and coping self-efficacy. The relationship between psychological states and psychological well-being was successfully mediated by coping self-efficacy (direct effects of -.31 to -.46 at p < 0.01) and resilience (direct effects of -.06 to -.26 at p < 0.01). Moreover, positive emotion significantly moderated depression (b = -.02, p < 0.01) and anxiety (b = -.14, p = 0.05) with psychological well-being. Findings highlighted the importance of these factors in developing a dedicated model to be built into the recovery plan to ameliorate the negative impact of COVID-19 on the psychological well-being. Hence, the Positive Emotion-Resilience-Coping Efficacy (PERCE) Model is developed.